2003
DOI: 10.1146/annurev.pharmtox.43.100901.135934
|View full text |Cite
|
Sign up to set email alerts
|

TheCaenorhabditis elegansDopaminergic System: Opportunities for Insights into Dopamine Transport and Neurodegeneration

Abstract: The neurotransmitter dopamine (DA) plays a central role in the coordination of movement, attention, and the recognition of reward. Loss of DA from the basal ganglia, as a consequence of degeneration of neurons in the substantia nigra, triggers postural instability and Parkinson's disease (PD). DA transporters (DATs) regulate synaptic DA availability and provide a conduit for the uptake of DA mimetic neurotoxins, which can be used to evoke neuronal death and Parkinson-like syndrome. Recently, we have explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 146 publications
0
71
0
2
Order By: Relevance
“…All of the genes responsible for DA biosynthesis, packaging, and reuptake have recognizable homologs in the worm genome, and genetic, cellular, and functional studies confirm their participation in dopaminergic function (47). Transcriptional green fluorescent protein (GFP) fusions allow the eight DA neurons to be clearly visible in vivo under a fluorescent dissecting scope, and, as in vertebrates, the neurotoxicants 6-hydroxy dopamine (6-OHDA), 1-methyl-4-phenylpyridinium, and rotenone can confer DA neurodegeneration (48,49).…”
mentioning
confidence: 91%
“…All of the genes responsible for DA biosynthesis, packaging, and reuptake have recognizable homologs in the worm genome, and genetic, cellular, and functional studies confirm their participation in dopaminergic function (47). Transcriptional green fluorescent protein (GFP) fusions allow the eight DA neurons to be clearly visible in vivo under a fluorescent dissecting scope, and, as in vertebrates, the neurotoxicants 6-hydroxy dopamine (6-OHDA), 1-methyl-4-phenylpyridinium, and rotenone can confer DA neurodegeneration (48,49).…”
mentioning
confidence: 91%
“…In addition, three pairs of gender-specific dopaminergic neurons are present in the male tail (Sulston et al, 1975). The mammalian neuronal proteins involved in DA synthesis, vesicle loading, and reuptake all have C. elegans homologs, and mutants for each of these homologs have been described previously (Wintle and Van Tol, 2001;Nass and Blakely, 2003). Sawin et al (2000) showed that exogenous DA has inhibitory effects on C. elegans motor behavior.…”
mentioning
confidence: 99%
“…elegans is a powerful genetic model for exploring the molecular mechanisms of neuron function and human disease (Riddle et al, 1997;Nass et al, 2001). The worm's nervous system contains almost all of the known signaling and neurotransmitter systems found in the vertebrates (Bargmann, 1998;Nass and Blakely, 2003). Its genome has been sequenced and contains approximately 20,000 genes, over 90% of the human genome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one forward genetic screen we could utilize our DAT-1::GFP reporter line to identify molecules involved in Mn 2+ -induced neuronal death. We would first mutagenize the genome of the parental animals and then isolate the second generation hermaphrodites (to homozygose the mutation; Nass et al, 2003) in which GFP is still retained in the DA neurons following exposure to Mn 2+ . Animals that have DA neurons that are insensitive to Mn 2+ could have mutations within Mn 2+ transport proteins or proteins involved in DA neuron viability or cell death.…”
Section: Discussionmentioning
confidence: 99%